0431 The contribution of molecular epidemiology to studying occupational disease: some accomplishments to date and opportunities for the future. (23rd June 2014) - Rothman, Nat; Vermeulen, Roel; Lan, Qing
Abstract : Objectives: There are several contributions that molecular epidemiology can make to the study of occupational disease. Method: These include 1) enhancing the ability to study dose-response relationships; 2) evaluating the biological plausibility that an exposure may be related to an adverse outcome; and 3) providing insight into the underlying biological mechanism of an established or suspected exposure-disease relationship. These goals can overlap at times. Results: There are multiple examples where molecular epidemiology studies have contributed important information about occupational exposures, including instances where such studies contributed data that played a role in determining if a given exposure was causally related to disease. Historically, these studies have complimented classic epidemiological investigations. Conclusions: There are multiple examples where molecular epidemiology studies have contributed important information about occupational exposures, including instances where such studies contributed data that played a role in determining if a given exposure was causally related to disease. Historically, these studies have complimented classic epidemiological investigations.